Holocene relative sea-level records from coral microatolls in Western Borneo, South China Sea - Majewski, Jędrzej M.; Switzer, Adam D.; Meltzner, Aron J.; Parham, Peter R.; Horton, Benjamin P.; Bradley, Sarah L.; Pile, Jeremy; Chiang, Hong-Wei; Xianfeng, Wang; Chiew, Tyiin Ng; Tanzil, Jani; Müller, Moritz; et al. (SAGE Publications, 2018)
The spatial variability of Holocene relative sea level (RSL) in the South China Sea is unknown, with data restricted to Thailand, the Malay Peninsula, and a few other isolated sites. In this study, we present new continuous RSL records for Borneo using surveyed and U–Th dated coral microatolls from four sites in western Sarawak. The record spans 450 years of RSL from 7450 to 7000 yr BP. Our data suggest that RSL was higher than present and rapid RSL rise had ceased by 7450 yr BP. We compare these RSL reconstructions with a regional model of glacial-isostatic adjustment (GIA). The RSL reconstructions from three sites off the coast of Sarawak show a spatial gradient opposite to that predicted by the GIA model. This disagreement can best be explained by tectonic deformation since 7000 yr BP, which was previously unrecognized. We propose vertical land motion of 0.7–1.45 m due to slip on the Serabang fault, which runs between our four sites. This slip may have occurred in response to the loading of the Sunda Shelf by rising sea level.